Adsorption of Protein‐Bound Uremic Toxins Through Direct Hemoperfusion With Hexadecyl‐Immobilized Cellulose Beads in Patients Undergoing Hemodialysis. Issue 1 (13th July 2017) - Yamamoto, Suguru; Sato, Mami; Sato, Yoko; Wakamatsu, Takuya; Takahashi, Yoshimitsu; Iguchi, Akira; Omori, Kentaro; Suzuki, Yasushi; Ei, Isei; Kaneko, Yoshikatsu; Goto, Shin; Kazama, Junichiro J.; et al.
Abstract: An accumulation of protein‐bound uremic toxins (PBUTs) is one of major reasons for development of uremia‐related complications. We examined the PBUT removal ability of a hexadecyl‐immobilized cellulose bead (HICB)‐containing column for patients undergoing hemodialysis. Adsorption of indoxyl sulfate (IS), a representative PBUT, to HICBs was examined in vitro. The HICB column was used in patients undergoing hemodialysis for direct hemoperfusion with a regular hemodialyzer. The serum IS, indole acetic acid (IAA), phenyl sulfate (PhS), and p ‐cresyl sulfate (PCS) levels were measured before and after passing the column. HICBs adsorbed protein‐free (free) IS in a dose‐ and time‐dependent manner in vitro (55.4 ± 1.4% adsorption of 1 millimolar, 251 µg/mL, IS for 1 h). In clinical studies, passing the HICB‐containing column decreased the serum level of free IS, IAA, PhS, and PCS levels significantly (by 34.4 ± 30.0%, 34.8 ± 25.4%, 28.4 ± 18.0%, and 34.9 ± 22.1%, respectively), but not protein‐bound toxins in maintenance hemodialysis patients. HICBs absorbed some amount of free PBUTs, but the clinical trial to use HICB column did not show effect to reduce serum PBUTs level in hemodialysis patients. Adsorption treatment by means of direct hemoperfusion with regular hemodialysis may become an attractive blood purification treatment to increase PBUT removal when more effective materials to adsorb PBUTs selectively will be developed.